A Comprehensive Meta-Analyses of the Nomological Network of Psychological Capital (PsyCap). (February 2023) - Loghman, Saeed; Quinn, Michael; Dawkins, Sarah; Woods, Megan; Om Sharma, Sumeet; Scott, Jenn
This paper presents the most rigorous meta-analysis undertaken to date of empirical literature examining antecedents and outcomes related to psychological capital (PsyCap), and moderators of these relationships. We investigated seven leadership styles as antecedents of PsyCap (authentic, ethical, servant, empowering, transactional, transformational, and abusive leadership), five outcomes (burnout, turnover intentions, work engagement, performance, and satisfaction), and the impact of four moderators (country of sample origin, cultural characteristics, industry type, and research design). Our analysis of PsyCap research (2007–2020) examined 244 studies (254 independent samples and over 96000 participants), which is over twice as large as previous PsyCap meta-analyses. To optimize the quality and reliability of findings, we corrected for artefacts and included heterogeneity, sensitivity, and publication bias analyses. Our results provide several new findings beyond previous PsyCap meta-analyses. We found that empowering, servant, transformational, and transactional leadership were all positively associated with PsyCap, with empowering and transformational leadership being the strongest antecedents of PsyCap and abusive and transactional leadership being the weakest. The findings demonstrated PsyCap was positively associated with work engagement, and negatively associated with burnout. Country of sample origin moderated all the relationships, except for servant and transactional leadership. Additionally, cultural characteristics (e.g., power distance, masculinity, long-term orientation, and uncertainty avoidance) moderated several conceptual relationships. Study design was also found to moderate the PsyCap—work engagement relationship. Collectively, these findings offer new and extended insights into the antecedents, outcomes, and moderators related to PsyCap, beyond previous meta-analyses. The theoretical and practical implications of these new findings are also discussed.